Reforming economic systems in development countries (Harvard University Press, 1991)
As economic transformation ripples through the former socialistic bloc and economic reform shapes the destinies of developing countries, questions concerning how economic systems are reformed and what role the government plays in that process have become central for the 1990's and beyond.